(untitled) (Contemporary Journal of Social Science Review, 2025)
Objectives: The study was undertaken to determine the association of perceived parental styles on the psychological distress of adolescents with deafness. Further, study investigates the association of resilience with psychological distress among adolescents with deafness. Sample and Method: Sample comprise of 100 adolescents (male = 50, female = 50). ages between 12-18 years. A convenient sampling method was used to collect data from different Special Education Schools situated in Lahore, Punjab. The Parental Authority Questionnaire (PAQBuri, 1991), Kessler Psychological Distress Scale (K10; Kesler, 2002), and Ego-Resiliency Scale (ERS; Block & Kreman, 1996) were used. Results: The results indicate that parenting styles i.e., authoritarian parenting style (r = .99, p<.001)), and permissive parenting style (r =-.51, p<.001) significantly associated with psychological distress among adolescents with deafness. However, it is not significantly associated with authoritative parenting style (r = -.14, p<.01). Further, Furthermore, resilience was significantly associated with psychological distress (r =–.17, p<.001) among adolescents with deafness. Conclusion: Resilience is one of the important factors in reducing psychological distress in adolescents. Furthermore, secure and healthy parenting styles also help in raising children as resilient and this can helps them to face the difficulties in their lives. Designing evidence based intervention targeting parenting practice is crucial for positive personality growth and development of adolescents.